Peran Korban dalam Tindak Pidana Penipuan Transaksi Elektronik: Perspektif Cyber Victimology - Maria Hera Agathea Manik; Andita Amelia; Akilah Putri Ibrahim; Muhammad Arsya Zaky; Fathia Aisya Zahra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The rapid growth of electronic transactions in Indonesia has driven a significant rise in digital fraud crimes employing social engineering methods that systematically exploit the psychological state of victims. As illustrated in the case of a victim identified by the initials AF, the perpetrator utilized emotional manipulation, false identity, and early-morning time pressure to undermine the victim’s critical thinking capacity, ultimately resulting in financial loss through a QRIS transfer. Existing legal scholarship has thus far failed to adequately explain the dynamics of the victim’s role in the cyber victimization process, as it remains dominated by a normative approach that positions the victim as a passive party. The purpose of this study is to analyze the role of victims in electronic transaction fraud through the lens of cyber victimology, as well as to examine the extent to which Indonesia’s criminal law framework accommodates the psychological and behavioral dimensions of victims. This study employs a normative juridical methodology with conceptual and case-based approaches, supported by empirical interview data from victims, analyzed in a descriptive-analytical manner by integrating Routine Activity Theory, Lifestyle-Exposure Theory, and the concept of victim precipitation as adapted to the context of cybercrime. The findings indicate that victims of electronic transaction fraud are not entirely passive; rather, they play an indirect role shaped by emotional conditions, limited time for verification, and systematic psychological exploitation by the perpetrator, which can be subsumed under Article 492 of the Criminal Code and Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the Electronic Information and Transactions Law (UU ITE). This study contributes to filling the conceptual gap between criminal law scholarship and cyber victimology in Indonesia, while also recommending the strengthening of victim protection mechanisms that consider psychological vulnerability as a relevant factor in cybercrime prevention policy.